1997
DOI: 10.1051/lait:199714
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SDS-PAGE profiles of four Belgian cheeses by multivariate statistics

Abstract: Summary -Most of the classification methods so far published for chee se varieties which are based either on rheological or compositional properties appear to be inadequate. Still, a promising approach in this area of cheese research is the application to proteolytic patterns of multivariate statistics such as principal component analysis (PCA) and discriminant analysis (DA). Both techniques were therefore performed on electrophoretic profiles obtained by sodium dodecyl sulphate-polyacrylamide gel electrophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Others who have used a statistical approach to differentiate cheese include: , who used DA of data from chemical analyses (water-soluble nitrogen (WSN), trichloroaceticacid-soluble nitrogen (TCA-SN), ammonia N, water activity (a w ), moisture, fat, salt and pH) to classify seven varieties of Spanish cheeses from the Canary Islands, with limited success; , who correctly classified 10 Spanish cheese types (eight samples of each type) using results from chemical analyses (TCA-SN, ammonia N, pH, NaCl and moisture content) that were statistically selected from a larger set of variables that also included total nitrogen (TN), a w and fat content; Dewettinck, Dierckx, Eichwalder, and Huyghebaert (1997), who found that, whereas PCA of data from sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) (Phast system) of the pH-4.6-insoluble protein fraction of four types of Belgian cheese sampled at different stages of maturity gave correct classification of two types and less clear differentiation of the other two types, DA gave correct classification of the four types. There was no clear differentiation of maturity using either method of data analysis.…”
Section: Differentiation Of Cheese Typementioning
confidence: 99%
“…Others who have used a statistical approach to differentiate cheese include: , who used DA of data from chemical analyses (water-soluble nitrogen (WSN), trichloroaceticacid-soluble nitrogen (TCA-SN), ammonia N, water activity (a w ), moisture, fat, salt and pH) to classify seven varieties of Spanish cheeses from the Canary Islands, with limited success; , who correctly classified 10 Spanish cheese types (eight samples of each type) using results from chemical analyses (TCA-SN, ammonia N, pH, NaCl and moisture content) that were statistically selected from a larger set of variables that also included total nitrogen (TN), a w and fat content; Dewettinck, Dierckx, Eichwalder, and Huyghebaert (1997), who found that, whereas PCA of data from sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) (Phast system) of the pH-4.6-insoluble protein fraction of four types of Belgian cheese sampled at different stages of maturity gave correct classification of two types and less clear differentiation of the other two types, DA gave correct classification of the four types. There was no clear differentiation of maturity using either method of data analysis.…”
Section: Differentiation Of Cheese Typementioning
confidence: 99%
“…The peptide pattern, as obtained by urea-PAGE or SDS-PAGE of the water soluble or insoluble fractions of cheeses, has been used as a fingerprint to discriminate between different cheese varieties (e.g., McGoldrik & Fox, 1999;Dewettinck, Dierckx, Eichwalder, & Huyghebaert, 1997).…”
Section: Primary Proteolysismentioning
confidence: 99%
“…Fractionation of cheese and its analysis by electrophoresis, chromatographic analysis of peptides and quantitative determination of free amino acids provide a more complete view of this phenomenon. Multivariate analysis has been proved to be very useful for the study and interpretation of all the data generated from various analytical methods (Dewettinck, Dierckx, Eichwalder, & Huyghebaert, 1996;Pripp, Rehman, McSweeney, & Fox, 1999).…”
Section: Introductionmentioning
confidence: 99%